1994
DOI: 10.1017/s0022215100126052
|View full text |Cite
|
Sign up to set email alerts
|

Sudden deafness in vestibular schwannoma

Abstract: Twelve per cent of a series of 284 patients with vestibular schwannoma presented with sudden deafness. If sudden sensorineural hearing loss is present then it is very likely to be the main presenting symptom. The mean length of patients' history is eight months shorter in this group than in the non-sudden deafness group. Sixteen per cent of vestibular schwannoma patients without sudden deafness present with a 'dead' ear whereas 29.5 per cent of those presenting with sudden deafness have total hearing loss. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 12 publications
(12 reference statements)
1
56
1
1
Order By: Relevance
“…This report describes a case of medulloblastoma in a 19-year-old man initially presenting with unilateral sudden sensorineural hearing loss. Unilateral sudden sensorineural hearing loss can be recognised as an initial symptom of brain tumor, but is most often associated with vestibular schwannomas 2,5,8,[11][12][13]18) . Sudden sensorineural hearing loss caused by medulloblastoma is extremely rare and, to our knowledge, there have been only three previous reports of medulloblastoma manifesting as sudden sensorineural hearing loss 6,7,9) .…”
Section: Discussionmentioning
confidence: 99%
“…This report describes a case of medulloblastoma in a 19-year-old man initially presenting with unilateral sudden sensorineural hearing loss. Unilateral sudden sensorineural hearing loss can be recognised as an initial symptom of brain tumor, but is most often associated with vestibular schwannomas 2,5,8,[11][12][13]18) . Sudden sensorineural hearing loss caused by medulloblastoma is extremely rare and, to our knowledge, there have been only three previous reports of medulloblastoma manifesting as sudden sensorineural hearing loss 6,7,9) .…”
Section: Discussionmentioning
confidence: 99%
“…88 The internal auditory artery or the labyrinthine artery (end artery) travels within the internal auditory canal, and it may be possible that vascular insult to it can result in sudden hearing loss. 11,60 However, if only vascular insult was the cause, one would also expect to see vestibular symptoms and cochlear hearing loss, which is not always the case. Further, due to the anatomical distribution of the blood supply to the cochlea, vascular compromise should result in low-frequency hearing loss in these patients, whereas mostly higher-frequency loss is reported in such cases.…”
Section: Sudden Hearing Lossmentioning
confidence: 99%
“…On the basis of our results with significant predominance of sudden hearing loss in premenopausal women at the time of their period, sudden hearing loss could be caused by vascular insufficiency of the cochlea or the eighth nerve. The most probable explanation of such a vascular cause may be tumour compression of the internal auditory artery (IAA) in the IAC [15,27]. Animal studies demonstrated that vascular occlusion may result in a variable distribution of histological damage in the cochlea and vestibular labyrinth, especially with temporary interruption of flow [26].…”
Section: The Impact Of Different Factors On Auditory Function Before mentioning
confidence: 99%
“…Moreover, * Part of this work was presented at the 2nd International Conference on Acoustic Neuroma Surgery, Paris, France, April 22-26. 1995 vestibular schwannomas were shown to express receptors for the female hormones oestrogen and progesterone [2,15]. Although intriguing, these correlations were not found consistently by all investigators and their significance remains unclear [12,14].…”
Section: Introductionmentioning
confidence: 99%